Age as a modulator of ionising radiation-induced cardiovascular disease - Whiteman, C (2024)
Cardiovascular disease (CVD), in particular atherosclerosis, remains the most common underlying cause of mortality worldwide. The link between ionising radiation (IR) and CVD has been well established; however, current evidence on whether age influences IR-induced CVD is limited. Furthermore, with links between CVD and senescence having been established, along with the potential of IR to induce senescence, it is plausible that IR-induced senescence may contribute to CVD development. In this thesis, I firstly demonstrate the novel use of the Ldl receptor knockout mouse (Ldlr-/-) model for investigation into IR-CVD. Secondly, I report that age does mediate the development of IR-CVD in two separate mouse models, the ApoE receptor knockout and Ldlr-/- models, with older mice developing IR-CVD. Thirdly, using human coronary artery endothelial cells (HCAECs) from donors ranging 17-55 years, I report IR-induced increases in adhesion and permeability, phenotypes that are pro-atherogenic. Notably, I report a correlation between SA-β-Gal activity and increasing HCAEC adhesion, along with the ability to ameliorate these effects by targeting senescence with rapamycin, supporting the hypothesis of IR-induced senescence promoting CVD. Finally, I present molecular profiles of the gene and protein changes associated with age, IR exposure, the modulation of IR-induced changes by age, and the effects of rapamycin on IR-induced changes. My findings provide evidence for age as a modulator of the effects of IR from animal models to functional in vitro assays, and down to human cell molecular expression profiles. Furthermore, the multi-omics performed provide a unique reference for ageing HCAECs.